The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.21203/rs.3.rs-1369739/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Th2-score in the tumor microenvironment as a predictive biomarker of response to BCG in patients with non-muscle invasive bladder carcinoma. A retrospective study.

Abstract: Intravesical BCG is the gold standard therapy for intermediate/high-risk NMIBC. However, the response rate is ~60%, and 50% of non-responders will progress to muscle invasive disease. BCG induces massive local infiltration of inflammatory cells (Th1), and ultimately cytotoxic tumor elimination. We searched for a predictive biomarker of BCG response by analyzing TILs polarization in the TME in pre-treatment biopsies. Materials and Methods: Pre-treatment biopsies from patients with NMIBC who received adequate in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…15 Simultaneously, obtaining the entire tumor specimen could assist pathologists in making more accurate diagnoses and facilitate the identification of histological variants that had a significant impact on the prognosis of patients with NMIBC. [40][41][42] Moreover, all pooled meta-analyses demonstrated that ERBT was associated with a lower incidence of residual tumor. These two pieces of evidence confirmed the sufficient efficacy of ERBT in managing NMIBC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15 Simultaneously, obtaining the entire tumor specimen could assist pathologists in making more accurate diagnoses and facilitate the identification of histological variants that had a significant impact on the prognosis of patients with NMIBC. [40][41][42] Moreover, all pooled meta-analyses demonstrated that ERBT was associated with a lower incidence of residual tumor. These two pieces of evidence confirmed the sufficient efficacy of ERBT in managing NMIBC.…”
Section: Discussionmentioning
confidence: 94%
“…Invasive detrusor muscle is the diagnostic criterion for NMIBC and MIBC 15 . Simultaneously, obtaining the entire tumor specimen could assist pathologists in making more accurate diagnoses and facilitate the identification of histological variants that had a significant impact on the prognosis of patients with NMIBC 40–42 . Moreover, all pooled meta‐analyses demonstrated that ERBT was associated with a lower incidence of residual tumor.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] About 3-quarters of bladder malignancies are non-muscle-invasive. [3] In contrast, 20% to 25% of bladder malignancies are muscle-invasive at the initial onset. [4,5] Patients with localized disease can be cured by surgical resection or radiotherapy, but this treatment is limited if the disease is recurrent or spread over long distances.…”
Section: Introductionmentioning
confidence: 99%